Nation-Building in the Post-Colonial Qatari State: The Politics and History of Nationalism - Zarqa Parvez (21841607) (2025)
This article examines the process of nation-building in post-colonial Qatar. By using a postcolonial lens, the study discusses the historical context of Qatar’s state formation, tracing the impact of colonialism and the role of external powers in shaping political structures and narratives. Through an analysis of key historical figures and events, such as Shaykh Jassim and the Qatari constitution, this article explores the use of tradition and indigenous modernity in the construction of Qatar’s national identity. By drawing on theoretical frameworks such as “invented traditions,” “imagined communities,” and the politics of tradition and modernity, the article provides a roadmap to understanding the main tenets of the national identity politics of Qatar today and key factors of its national identity narratives, including ethno-political migrations, citizenship dynamics, and institutional frameworks established by the state constitution. It argues that while nation-building processes may share commonalities across different geographies, the specific historical, cultural, and political dynamics of Qatar shaped its unique trajectory. Ultimately, the article contributes to a deeper understanding of the complexities of nation-building in post-colonial contexts and the construction of national identity in the Gulf region. Other Information Published in: Review of Middle East Studies License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1017/rms.2024.32